If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6 = 1 + -2x Reorder the terms: -6 + 5x = 1 + -2x Solving -6 + 5x = 1 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6 + 5x + 2x = 1 + -2x + 2x Combine like terms: 5x + 2x = 7x -6 + 7x = 1 + -2x + 2x Combine like terms: -2x + 2x = 0 -6 + 7x = 1 + 0 -6 + 7x = 1 Add '6' to each side of the equation. -6 + 6 + 7x = 1 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 1 + 6 7x = 1 + 6 Combine like terms: 1 + 6 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| (a+3b)x+(a+3b)y= | | 8b+3b-6=38 | | 0.6666666666x-4=10 | | -2x+8=-6+5 | | -2(-10)-y=16 | | x+y=630 | | 6s-2=5s+10 | | 12-.6x=-27 | | (16x+5y)dx+(3x+y)dy=0 | | x*x=-36 | | 2x^3-8x^2-14x= | | 10x=4.09 | | n^3-n-3360=0 | | e^1-7x=9 | | (6-v)(3v-4)=0 | | x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 | | -7=p-5 | | 6s^2+3s=0 | | 802.1-4.82+9= | | y-9=-19 | | 4r^2+30r+10=0 |